Credit Exemption Management System (CEMS) / Siti Fairuza Hassam ... [et al.] - Hassam, Siti Fairuza; Hassan, Nur Diana; Hassan, Hasroleffendy; Harudin, Syahmi; Mustapha, Yanti Aspha Amiera (2021)
Credit Exemption Management System (CEMS) is smartly designed to provide a comprehensive study plan and to recommend the guidelines for credit transfer that are equivalent on credit values for qualifications in the Institute of Higher Learning (IHL). The exemption process is a part of the credit requirement for bachelor’s degree programs based on the existing qualification which is identified as equal with the degree from Universiti Teknologi MARA (UiTM) specifically. This system is created from the advanced Microsoft Excel 365 version which provides the integrated database system for students to track their study plan for the whole semester and determine those courses that are equivalent to get transferred efficiently. Traditionally, the process requires students to fill in the credit exemption form and determine those courses that allow to transfer as credit exemption based on the list stated in the Manual of Credit Exemption Guideline provided by Faculty. However, the students found this process difficult to understand and it would result in the forms to be filled in incorrectly. This will halt many other processes such as the assignment of group, course registration and such. Detailed scrutiny needs to be given to the students to guide them in filling the form and ensure that they are able to execute the credit exemption process successfully. Therefore, the introduction of the CEMS system is expected to help students to manage their Credit Exemption process at their fingertips. To begin, this system will only be implemented specifically for new students entering the Degree in the Faculty of Management and Business at Kedah branch. The system is expected to be effective in achieving the objectives as stated and it is hoped that it will also be beneficial to students as a whole.